Variation in lung cancer resources and workload: results from the first national lung cancer organisational audit. Issue 10 (4th June 2015) - Cusworth, K; O'Dowd, E; Hubbard, R; Beckett, P; Peake, M D; Woolhouse, I
Abstract : We report the findings of the first national lung cancer organisational audit. The results demonstrate marked variation in service provision and workload of some lung cancer specialists. For example, over half of the clinical nurse specialists report case volumes over recommended numbers. Some trusts have no access to key treatments such as video assisted thoracoscopy (VAT) lobectomy and stereotactic radiotherapy. Multivariate regression analysis demonstrated an association between higher surgical resection rates and the on-site availability of advanced staging and therapeutic modalities, for example, PET scan and VAT lobectomy. We conclude by making a number of recommendations to address the variation in lung cancer care.